Cover Image, Volume 84, Issue S1. (September 2016) - Moult, John; Fidelis, Krzysztof; Kryshtafovych, Andriy; Schwede, Torsten; Tramontano, Anna
Abstract : Model TS064_1 of a new‐fold CASP11 target T0806 superimposed on the target structure, YaaA from E. coli K‐12 (RMSD to target 3.6 Å ); Structure of the very different best available template (PDB ID 2q07)., DOI:10.1002/prot.25064 .